DESKRIPSI KONDISI HABITAT SIAMANG, Symphalangus syndactylus, DI HUTAN LINDUNG REGISTER 28 PEMATANG NEBA KABUPATEN TANGGAMUS - Bunga Indah Permatasari; Agus Setiawan; Arief Darmawan (Scripta Biologica, 2017)
The Siamang, Symphalangus syndactylus, an arboreal black-furred gibbon member of the family Hylobatidae is listed as an endangered species by IUCN since 2008. The main threat to Siamang is the degraded habitat in term of quality and extent due to fragmentation. Protected forest Register 28 Pematang Neba located in Kabupaten Tanggamus is an example of the Siamang habitat threatened by the surrounding land conversion. This study aimed to determine the vegetation structure and profile of the Siamang habitat and to determine the diversity and abundance of plants the diet of Siamang. This study was a survey, and the observation was conducted from July to August 2017 applying three belt transect in the Protected Forest Register 28 Pematang Neba. The vegetation structure and profile of the Siamang habitat showed the distance between trees was more than 4 m that influence the Siamang activity in foraging, resting, and playing. The IVI showed a moderate category at the level of 130.813%, 135.948%, and 122.98% for habitat 1, 2, and 3 accordingly. The diversity index showed a moderate category at the level of 2.905 and 2.762 for habitat 1 and 2 respectively, and a high category for habitat 3 at the level of 3.066. The similarity index values among habitats were considered high (69-81%) allowing Siamang to migrate between habitats. The variety of Siamang diet was composed of leaves, fruits, and flowers.